mVOC: a lightweight environmental data and air samples acquisition system to install in captive balloons - Fonseca, José
One of the current research work in environmental science is the study of the impact of polluting substances such as Volatile Organic Compounds (VOCs) generated in coastal regions where human activity is more intensive in inland regions. In fact, due to maritime breezes, the effect of pollution is often sensed far away from the local that originates it. The VOCs distribution depends on the height and meteorological parameters, such as temperature, pressure and relative humidity. Therefore these parameters must be measured in a vertical plan to a correct pollution characterization. In this paper a specific small system for acquiring VOCs and meteorological parameters is presented. The system was developed in order to be suitable for use in a small helium balloon with low weight capacity. No electronic commercial system is available with the desired characteristics for this purpose. The system is lightweight, acquires product samples with constant airflow control, and performs temperature, pressure and humidity data acquisition. The system uses a small microcontroller and some specific techniques to avoid loosing data during operation. It is also a very low-cost system which is an important issue due to the high risk of damage or lost. The paper describes implementation details and results from the experiments carried on with the prototypes.